The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1002/lt.21041
|View full text |Cite
|
Sign up to set email alerts
|

Low risk of hepatitis B virus recurrence after withdrawal of long-term hepatitis B immunoglobulin in patients receiving maintenance nucleos(t)ide analogue therapy

Abstract: Hepatitis B virus (HBV) recurrence rates of 0-16% had been reported in patients maintained on nucleoside analogues (NA) after hepatitis B immunoglobulin (HBIG) discontinuation after orthotopic liver transplantation (OLT). However, follow-up in most studies was short. We aimed to determine the long-term risk of HBV recurrence using this strategy. All HBV patients who received Ն7 doses of intravenous HBIG after OLT, with no HBV recurrence while receiving HBIG, and who eventually discontinued HBIG and were mainta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(92 citation statements)
references
References 45 publications
4
86
0
2
Order By: Relevance
“…We obtained similar results with the same protocol in living donor liver transplant recipients, too [15 Anna Lok has rewieved results of 12 studies of prophylactic combination therapy with HBIG and lamivudine, and reported that post-transplant HBV recurrence was observed in only 7/168 (4%) patients during a mean follow-up of 13-22 months [16].…”
Section: Hbig Plus Lamivudinesupporting
confidence: 61%
“…We obtained similar results with the same protocol in living donor liver transplant recipients, too [15 Anna Lok has rewieved results of 12 studies of prophylactic combination therapy with HBIG and lamivudine, and reported that post-transplant HBV recurrence was observed in only 7/168 (4%) patients during a mean follow-up of 13-22 months [16].…”
Section: Hbig Plus Lamivudinesupporting
confidence: 61%
“…When NAs are used as a part of a pro phylaxis regimen, the effect of lowdose IM HBIg is equi valent to that of highdose IV HBIg [5,6] , and maintaining LMV treatment alone always results in a low risk of HBV recurrence, regardless of HBIg discontinuance.Moreover, even one week of HBIg combined with lamivudine re gimen at the beginning of the treatment had an equiva lent effect, compared with a longterm highdose HBIg regimen for preventing hepatitis B recurrence [13] . It is sug gested that with adequate treatment of potent NAs, con comitant indefinite passive immunization may not be essential [14] . Some studies have compared complete HBIgfree NAs monotherapy (without a short initial HBIg phase) with combined therapy, describing 24 year recurrence rates of about 15%40%, higher than those of the combi nation therapy [1519] .…”
Section: Discussionmentioning
confidence: 99%
“…ETV and TDF should be preferred. PegIFN treatment should not be used because of its low efficacy and its serious adverse effects (47)(48)(49)(50)(51)(52)(53)(54)(55).…”
Section: Xxi-hbv Prophylaxis and Treatment After Liver Transplantationmentioning
confidence: 99%